Gambaran Karakteristik Gagal Ginjal Kronik Obstruktif dan Non-obstruktif pada Pasien Dewasa-Lansia di RSUD Raden Mattaher Tahun 2017-2020 - Salsabila, Amalya; Herman, Hendra; Shafira, Nyimas Natasha Ayu; Fauzan, Randy; Wulandari, Putri Sari (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
ABSTRACT Background: Chronic kidney failure is a clinical condition in which the estimated or measured Glomerular Filtration Rate (GFR) is <60 mL/min/1.73 m2. This study aims to describe the characteristics of patients with chronic obstructive and non-obstructive kidney failure in the adults-elderly at Raden Mattaher Hospital in 2017-2020. Methods: This research is a quantitative descriptive type with a cross-sectional study design with a retrospective approach through the medical records of chronic kidney failure patients in 2017-2020 at Raden Mattaher Hospital with a total of 90 samples. Results: Based on ages, early adulthood (10%), late adults (25.6%), early elderly ( 21.1%), and the elderly (43.3%). Based on gender, male patients (62.9%) and female patients (31.1%). Patients with chronic kidney failure with non-obstructive trigger disease, namely hypertension (7.8%). Most chronic kidney failure patients with obstructive trigger disease were kidney stones (38.9%). Conclusion: Most patients with chronic kidney failure at Raden Mattaher Hospital in 2017-2020 were in the age range of 56-65 years (late elderly) and were male. The most common non-obstructive chronic kidney failure trigger disease is hypertension. The most common cause of obstructive chronic kidney failure is kidney stones. Keywords: Chronic kidney failure, Obstructive kidney failure, Non-obstructive kidney failure ABSTRAK Latar Belakang: Gagal ginjal kronik merupakan keadaan klinis dimana Laju Filtrasi Glomerulus yang diperkirakan adalah <60 mL/min/1,73 m2. Penelitian ini bertujuan untuk mengetahui gambaran karakteristik pasien gagal ginjal kronik obstruktif dan non-obstruktif pada dewasa-lansia di RSUD Raden Mattaher tahun 2017-2020. Metode: Penelitian ini penelitian deskriptif kuantitatif dengan desain penelitian cross sectional pendekatan retrospective melalui rekam medis pasien gagal ginjal kronik tahun 2017-2020 di RSUD Raden Mattaher sebanyak 90 sampel. Hasil: Berdasarkan usia, dewasa awal (10%), dewasa akhir (25,6%), lansia awal (21,1%), dan lansia akhir (43,3%). Berdasarkan jenis kelamin, laki-laki (62,9%) dan perempuan (31,1%). Pasien gagal ginjal kronik dengan penyakit pemicu bersifat non-obstruktif yaitu hipertensi (7,8%), dan yang bersifat obstruktif paling banyak yaitu batu ginjal (38,9%). Kesimpulan: Sebagian besar pasien gagal ginjal kronik di RSUD Raden Mattaher tahun 2017-2020 dalam rentang usia 56-65 tahun (lansia akhir), berjenis kelamin laki-laki. Penyakit pemicu gagal ginjal kronik non-obstruktif paling banyak yaitu hipertensi, sedangkan penyakit pemicu gagal ginjal kronik obstruktif paling banyak yaitu batu ginjal. Kata Kunci: Gagal ginjal kronik, Gagal ginjal obstruktif, Gagal ginjal non-obstruktif